Development of hand-arm model rig for tremor excitation - As'arry, A.; Md. Zain, M. Z.; Hussien, M.; Mailah, Musa; Abdullah, M. Y.; Ahmad, R.; Kazi, S. (2008)

(untitled)
This paper describes the development of a handarm model rig to simulate human tremor behaviour. The experimental rig is designed as an apparatus to induce vibration along a hand-arm model. An Intra Vernacular (IV) Training arm is used as the handarm model. Displacement and acceleration behaviour at three selected points along the handarm model were recorded by mean of piezoelectric accelerometer. The data from the experiment can be used for further analysis of the human hand-arm tremor especially for Parkinson's disease (PD) patients. Results from the experiments are raw data which can later be used in designing an appropriate instrument that can suppress the hand tremor.